PROBLEM SOLVING USING ORDER OF OPERATIONS

When two or more operations are carried out, which can be performed first.

To avoid this confusion, our mathematicians has found some set of rules followed in order of operations.

BEDMAS OR PEMDAS

Perform operations within the Bracket or Parenthesis first.

Calculate Exponents.

Starting from left to right perform division or multiplication, whichever comes first.

Finally from left to right perform addition or subtraction, whichever comes first.

Example 1 :

Evaluate :

35 - 10 ÷ 2 x 5 + 3

Solution :

35 - 10 ÷ 2 x 5 + 3

We don't have brackets or parenthesis in this problem.

35 - 10 ÷ 2 x 5 + 3 (Division)

35 - 5 x 5 + 3 (Multiplication)

35 - 25 + 3 (Subtraction)

= 13

Example 2 :

Evaluate :

2(3 x 6 - 4) + 7

Solution :

2(3 x 6 - 4) + 7

2(3 x 6 - 4) + 7

(Inside the bracket performing multiplication)

= 2(18 - 4) + 7

(Inside the bracket performing subtraction)

2 x 14 + 7 (Multiplication)

= 28 + 7

= 35

Example 3 :

Evaluate :

5 + 4 x 7 + 27 ÷ 9

Solution :

= 5+ 4 x 7 + 27 ÷ 9 (Multiplication comes first)

= 5 + 28 + 27 ÷ 9 (Division)

= 5 + 28 + 3 (Addition)

= 36

Example 4 :

Evaluate :

4 x 3- (3 + 2)2

Solution :

4 x 3(3 + 2)2 (Bracket)

4 x 3 - (5) (Exponents)

4 x 9 -  25 (Multiplication)

36 - 25 (Subtraction)

= 11

Example 5 :

Evaluate :

(7-3 x 2) ÷ (8 ÷ 4 - 1)

Solution :

(7- 3 x 2÷(8 ÷ 4 - 1)

(7 - 6) ÷ (8 ÷ 4 - 1)

(7 - 6) ÷ (2 - 1)

= 1 ÷ 1

= 1

Example 6 :

Evaluate :

19 - [{3 x 7} - {9 ÷ 3}] + 14

Solution :

= 19 - [(3 x 7) - (9 ÷ 3)] + 14

= 19 - [21 - (÷ 3)] + 14

= 19 - [21 - 3+ 14

= 19 - 18 + 14

= 19 - 18 + 14

= 15

Example 7 :

Evaluate :

4 x [(4 x 3) ÷ 2] x 7

Solution :

= 4 x [(4 x 3÷ 2] x 7

= 4 x [12 ÷ 2] x 7

= 4 x 6 x 7

= 168

Example 8 :

Evaluate :

5 + [6 + (7 x 2)] ÷ 5

Solution :

= 5 + [6 + (7 x 2)] ÷ 5

= 5 + [6 + 14÷ 5

= 5 + 20 ÷ 5

= 5 + 4

= 9

Example 9 :

Evaluate :

5 x 2+ 2 x 32

Solution :

= 5 x 22 + 2 x 32

=  5 x 4 + 2 x 9

= 20 + 18

=  38

Example 10 :

Evaluate :

3 - 2÷ 2 + 1

Solution :

= 3 - 22 ÷ 2 + 1

= 3 - ÷ 2 + 1

= 3 - 2 + 1

= 1 + 1

= 2

Kindly mail your feedback to v4formath@gmail.com

Recent Articles 1. Trigonometry Word Problems Worksheet with Answers

Jan 17, 22 10:45 AM

Trigonometry Word Problems Worksheet with Answers

2. Trigonometry Word Problems with Solutions

Jan 17, 22 10:41 AM

Trigonometry Word Problems with Solutions